Geologia e Geoquímica (ETR e Inclusões Fluidas) das Mineralizações (F, BA) da Parte Norte do Distrito Fluorítico de Santa Catrina, Sul do Brasil - DA ROCHA, FLÁVIO FRANÇA; NETO, ARTHUR CÉZAR BASTOS (Pesquisas em Geociências, 1999)
This work deals on the fluorite deposits from the Grão Pará (GP) and Rio Bravo Alto (RBA) veins systems both situated at the northern part of Santa Catarina Fluorite District. The GP deposits are controlled by an ancient shear zone. Ore deposition is related to two tectonic phases: (1) dextral transtensive reactivation related to a NE/SW compression; deposition of green-purple massive or coarse banded fluorite; tectonic and hydraulic breccias assign successive transitions from hydrostatic to tectonic regimes; the ore was affected by latter silicification; (2) reactivation as normal fault, related to a extensional tectonic; deposition of purple and yellow banded fluorite, collapse breccias and cocardes. First phase fluorite was deposited at temperatures decreasing from 170º to 120ºC; silicification temperature is around 140ºC. Second phase fluorite was deposited at temperatures between 140º and 120ºC. The fluid inclusions salinity range from 0 to 2% eq. NaCl. The isotopic composition of water from primary fluid inclusions in the fluorite at RBA (δD ͌ -60‰ SMOW) is typical of meteoric water from interior continental region. The RBA fluorite has the same HREE signature as fluorite from the southern district deposits and regional granites. REE and fluid inclusion data reject a link with alkaline magmatism. Fluorine was leached from accessory fluorite of regional granites. The fluorite deposition was connected to a single hydrothermal event correlated to the earlier hydrothermal event described at the southern district.